Photocatalytic Activity of Polymer Nanoparticles Modulates Intracellular Calcium Dynamics and Reactive Oxygen Species in HEK-293 Cells - Bossio, Caterina; Abdel Aziz, Ilaria; Tullii, Gabriele; Zucchetti, Elena; Debellis, Doriana; Zangoli, Mattia; Di Maria, Francesca; Lanzani, Guglielmo; Antognazza, Maria Rosa (Frontiers in Bioengineering and Biotechnology, 2018)
Optical modulation of living cells activity by light-absorbing exogenous materials is gaining increasing interest, due to the possibility both to achieve high spatial and temporal resolution with a minimally invasive and reversible technique and to avoid the need of viral transfection with light-sensitive proteins. In this context, conjugated polymers represent ideal candidates for photo-transduction, due to their excellent optoelectronic and biocompatibility properties. In this work, we demonstrate that organic polymer nanoparticles, based on poly(3-hexylthiophene) conjugated polymer, establish a functional interaction with an in vitro cell model (Human Embryonic Kidney cells, HEK-293). They display photocatalytic activity in aqueous environment and, once internalized within the cell cytosol, efficiently generate reactive oxygen species (ROS) upon visible light excitation, without affecting cell viability. Interestingly, light-activated ROS generation deterministically triggers modulation of intracellular calcium ion flux, successfully controlled at the single cell level. In perspective, the capability of polymer NPs to produce ROS and to modulate Ca2+ dynamics by illumination on-demand, at non-toxic levels, may open the path to the study of biological processes with a gene-less approach and unprecedented spatio-temporal resolution, as well as to the development of new biotechnology tools for cell optical modulation.